The Microwave Pretreatment Effects on Yield and Tocopherol Content of Cold-Pressed Sesame Oil - Wilaipon, Patomsok (Naresuan University Engineering Journal, 2023)
The benefits of black sesame have long been recognized, and black sesame has been used for consumption, cosmetics for hair and skin care, and medication. One process used to produce high quality black sesame oil is the cold pressed process, where temperature is controlled to be lower than 60 oC throughout the process. However, this process results in a lower yield than extraction by solvent. Therefore, with the aim of enhancing efficiency, this study is examining the impact of a microwave pretreatment on the output of cold pressing black sesame oil. The experiment tested three conditions, with different microwave wattages and pretreatment durations, while temperatures were controlled slightly below 60 oC under all conditions. The effects of microwave pretreatment on seed color and weight loss profile of black sesame were studied. Tocopherol, one of the significant compounds of sesame oil, was also examined. It was found that under all conditions, microwave pretreatment increased yields from black sesame cold pressing by 8% relative to pressing with no pretreatment. In addition, higher g+β tocopherolin levels were found in the black sesame oil extracted after the pretreatment process, and the highest g+β tocopherol levels were found after using low microwave wattage with a longer duration of pretreatment. It was also found that the weight loss rate of black sesame seed increased as the microwave power was increased. Besides, as compared to the non-activated one, 180 W sesame seed showed the highest value of color difference.